A PFAS-selective semifluoroalkylated polyvinylimidazolium resin for reversible adsorption of anionic fluorosurfactants - Judith Schobel; Johanna Freilinger; Jana Marx; Madeleine Larch; Martin Spruck; Raphael Plangger; Marco Rupprich; Herwig Schottenberger; Christian W. Huck; Rania Bakry; Jan O. Back (Water Research, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Scoring and distribution of cartilage degeneration and osteophytosis in cervical facet joint arthrosis in warmblood horses with and without wobbler - W. Bergmann; T. Spoormakers; S. Veraa; W. Back; K. Vanderperren; C. Delessalle; I. Wijnberg; S. Journée; H. Journée; H. Vernooij; A. Gröne; G. Grinwis (Journal of Comparative Pathology, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Differentiating between point and non-point source nutrient loadings of wastewater in an agriculturally impacted area using a hybrid statistical model - Jordan T. Jatko; Ryan A. McManamay; Megan T. Woodyard; Lydia K. Roush; Jeffrey A. Back; Ryan S. King; Cole W. Matson (Science of The Total Environment, 2024)

Estimating the influence of carbonates in the stable isotopic values of suspended particulate organic matter: implications in ecological studies - Bianca Possamai; Jeffrey A. Back; Charles M. Mansfield; Zach S. Moran; Renan C. Machado; Cole W. Matson (Aquatic Sciences, 2023)

Diazotrophy modulates cyanobacteria stoichiometry through functional traits that determine bloom magnitude and toxin production - Nicole D. Wagner; Felicia S. Osburn; Raegyn B. Taylor; Jeffrey A. Back; C. Kevin Chambliss; Bryan W. Brooks; J. Thad Scott (Limnology and Oceanography, 2023)
Harmful cyanobacterial blooms are an increasing threat to water quality. The interactions between two ecophysiological functional traits of cyanobacteria, diazotrophy (nitrogen [N]‐fixation) and N‐rich cyanotoxin synthesis, have never been examined in a stoichiometric explicit manner. We explored how a gradient of resource N : phosphorus (P) affects the biomass, N, P stoichiometry, light‐harvesting pigments, and cylindrospermopsin production in a N‐fixing cyanobacterium, Aphanizomenon . Low N : P Aphanizomenon cultures produced the same biomass as populations grown in high N : P cultures. The biomass accumulation determined by carbon, indicated low N : P Aphanizomenon cultures did not have a N‐fixation growth trade‐off, in contrast to some other diazotrophs that maintain stoichiometric N homeostasis at the expense of growth. However, N‐fixing Aphanizomenon populations produced less particulate cylindrospermopsin and had undetectable dissolved cylindrospermopsin compared to non‐N‐fixing populations. The pattern of low to high cyanotoxin cell quotas across an N : P gradient in the diazotrophic cylindrospermopsin producer is similar to the cyanotoxin cell quota response in nondiazotrophic cyanobacteria. We suggest that diazotrophic cyanobacteria may be characterized into two broad functional groups, the N‐storage‐strategists and the growth‐strategists, which use N‐fixation differently and may determine patterns of bloom magnitude and toxin production in nature.

Chemical fingerprinting of the Brazilian medicinal plant Calea pinnatifida (R. Br.) Less. (Asteraceae) collected at different altitudes - Franciely Vanessa Costa; Alice Gadea; Altamir Rocha Antunes; Solenn Ferron; Álvaro José Back; James W. Barlow; Vanilde Citadini-Zanette; Françoise Lohézic-Le Dévéhat; Patrícia de Aguiar Amaral (Natural Product Research, 2022)

Growth and carbon stock change in eucalypt woodlands in northeast Australia: ecological and greenhouse sink implications - W. H. Burrows; B. K. Henry; P. V. Back; M. B. Hoffmann; L. J. Tait; E. R. Anderson; N. Menke; T. Danaher; J. O. Carter; G. M . McKeon (Global Change Biology, 2002)
Data from 57 permanent monitoring sites are used to document the growth in woody vegetation and estimate the carbon sink in 27 M ha of eucalypt woodlands (savannas), contained within c. 60 M ha of grazed woodlands in Queensland (northeast Australia). The study sites are shown to be representative of the environment and structure of the eucalypt woodlands in the defined study area. Mean basal area increment for all live woody plants in 30 long‐term sites, with an average initial basal area of 11.86 ± 1.38 (SE) m 2 ha −1 , was 1.06 m 2 ha −1 over a mean 14 years timeframe. The majority of the measurement period, commencing between 1982 and 1988, was characterized by below‐average rainfall. The increase in live tree basal area was due primarily to growth of existing trees (3.12 m 2 ha −1 ) rather than establishment of new plants (0.25 m 2 ha −1 ) and was partly offset by death (2.31 m 2 ha −1 ). A simple but robust relationship between stand basal area and stand biomass of all woody species was developed for the eucalypt dominant woodlands. Analysis of above‐ground carbon stocks in live and standing dead woody plants gave a mean net above‐ground annual carbon increment for all 57 sites of 0.53 t C ha −1 y −1 , similar to values estimated elsewhere in world savannas. Published root : shoot ratios were used to infer C flux in woody root systems on these sites. This results in an estimated sink in above‐ and below‐ground biomass of 18 Mt C y −1 over the eucalypt woodlands studied, and potentially up to 35 Mt C y −1 if extended to all grazed woodlands in Queensland. It is suggested that introduction of livestock grazing and altered fire regimes have triggered the change in tree‐grass dominance in these woodlands. Thus, change in carbon stocks in the grazed woodlands of Queensland is identified as an important component of human‐induced greenhouse gas flux in Australia, equivalent in magnitude to c . 25% of the most recently published (1999) total estimated national net emissions. The latter inventory takes into account emissions from land clearing, but does not include the sink identified in the present study. This sequestration also represents a small but significant contribution to the global terrestrial carbon sink.

Subcellular localization of hepatitis C viral proteins in mammalian cells - J.-E. Kim; W. K. Song; K. M. Chung; S. H. Back; S. K. Jang (Archives of Virology, 1999)

Chirp (2–7 kHz) echo characters in the Ulleung Basin - S. K. Chough; S. H. Lee; J. W. Kim; S. C. Park; D. G. Yoo; H. S. Han; S. H. Yoon; S. B. Oh; Y. B. Kim; G. G. Back (Geosciences Journal, 1997)

An ELISA for detection of antibodies against influenza A nucleoprotein in humans and various animal species - G. F. de Boer; W. Back; A. D. M. E. Osterhaus (Archives of Virology, 1990)